Photocatalytic degradation of phenol in a simulated oil fields produced water and potential reuse for agriculture purposes - Omer Mohammed, Al-Haiqi (2022)
Large volume of wastewater often known as “produced water” are usually generated during the processing of oil and gas production. This produced water is commonly regarded as a high-volume toxic waste, which needed to be appropriately treated to meet the stipulated standard before being discharged or used for other purposes. The treatment of produced water is very important due to legislation and environmental concerns. Produced water poses a unique and complex treatment problem, treating oil field produced water prior to discharge may become increasingly difficult due to the limitations of the conventional treatment technologies. In this study, the use of ZnO/Fe2O3 nanocomposite as photocatalysts for the degradation of toxic pollutants in oil field produced water has been investigated. ZnO/Fe2O3 nanocomposite was prepared by sol-gel method and characterized by X-ray diffraction analysis (XRD), Transmission electron microscope (TEM), Field Emission, Scanning Electron Microscope (FESEM), N2 physisorption analysis, Ultra-Violet-Visible Spectroscope and Thermogravimetric Analyzer (TGA). The photocatalytic activity of the ZnO/Fe2O3 nanocomposite was examined using the degradation of the phenol in the simulated oil field produced water under direct sunlight. The effects of parameters such as the irradiation time, initial phenol concentration, pH and ZnO/Fe2O3 dosage on the phenol degradation were examined and optimized using response surface methodology and Box-Behnken Design. The study shows that all the three parameters had significant influence on the phenol degradation from the simulated oil field produced water. However, the analysis of variance (ANOVA) shows that the effects of the parameters on the percentage phenol can be ranked as irradiation time > initial phenol concentration, ZnO/Fe2O3 dosage > pH. The interaction between the parameters were observed to have substantial effect phenol degradation. At the optimum conditions of 176 min, 3 mg/L, 4.34, and 4.11 mg/L for irradiation time, initial phenol concentration, pH and ZnO/Fe2O3 dosage, 92.56% phenol was degradation from the modelled produced water. The predicted value of 92.56% obtained from the RSM model is consistent with the validated values of 93.29% with a residual of 0.73%.